Menstrual changes after COVID-19 vaccination among menstruators of reproductive age: A cross- sectional study from Erbil City, Iraq. - Warda Hassan Abdullah (Public Library of Science (PLoS), 2024)
The COVID-19 vaccination has been reported to have various post-vaccination effects, including potential changes in the menstrual cycle among menstruators of reproductive age. The aim of this study is to investigate the relationship between COVID-19 vaccination and menstrual changes among menstruators within Iraqi society and contribute to the knowledge about COVID-19 vaccine-related menstrual changes. The cross-sectional study involved a sample of 400 menstruators residing in Erbil City, Kurdistan Region, Iraq. The study specifically focused on individuals who were both infected and uninfected by COVID-19 and had received the COVID-19 vaccine. Individuals with hormonal diseases or those who had undergone hormonal therapy were excluded from the study. To ensure representation from different areas of Erbil City, the study was conducted in four primary healthcare centers selected based on geographic direction: South, East, North, and West sides. The author utilized a structured questionnaire to assess and compare changes in the menstrual cycle before and after receiving the COVID-19 vaccine. The study found that a significant proportion (71.8%) of the participants experienced menstrual changes after receiving the COVID-19 vaccination, particularly after receiving both doses. These changes included alterations in the characteristics and symptoms of the menstrual cycle compared to before vaccination. The findings suggest that the COVID-19 vaccination can potentially affect the menstrual cycle in women of reproductive age. In conclusion, by revealing distinct changes in cycle characteristics and symptomatology, the study findings contribute to an expanding body of evidence supporting the connection between vaccination and menstrual alterations. Future studies with larger sample sizes and diverse populations are warranted to validate and expand upon the results of this study.